Fabrication of Multifunctional Composite Nanofibers by Green Electrospinning - Edurne González; Aitor Barquero; Maria Paulis; Jose Ramon Leiza (Macromolecular Materials and Engineering, 2023)
Abstract The present work takes advantage of green electrospinning to create novel composite multifunctional nanofibers (NFs) bearing inorganic nanoparticles (NPs), more specifically quantum dots (QDs), cerium oxide nanoparticles (CeO2 NPs) and iron oxide nanoparticles (Fe3O4 NPs). This is achieved by first encapsulating the desired inorganic NPs into polymer particles by the use of miniemulsion polymerization, and second, spinning the hybrid polymer particles using polyvinyl alcohol (PVA) as template polymer. It is proved that using green electrospinning, it is not only possible to ensure an excellent distribution and encapsulation of the inorganic NPs along the NFs, but also allows to control and change the concentration, size, and type of the inorganic NPs without altering the NFs size, a fact that is not possible by conventional solution electrospinning. As proof of concept, NFs with up to three different types of inorganic NPs have been created in a single electrospinning step, but this technology allows to incorporate as much inorganic NPs as desired without altering the NFs morphology and ensuring a good distribution and encapsulation of the NPs. This paper demonstrates that green electrospinning is a powerful and attractive technology to create multifunctional NFs that are promising materials for sensing and biomedical applications.